THE IMPACT OF CAFFEINE ON SURGERY - Weronika Ewa Nowak; Paweł Harbut; Aleksander Białoń; Dominika Walczak; Adrian Kruk; Katarzyna Jakubowska; Aleksandra Dorosz; Igor Gawłowski; Aleksandra Miśta; Lidia Jurczenko (International Journal of Innovative Technologies in Social Science, 2026)
Caffeine is one of the most widely consumed psychoactive substances and is commonly used by both surgical patients and healthcare professionals. While its primary effect on the central nervous system is the reduction of fatigue and enhancement of alertness, caffeine also influences cardiovascular function, skeletal muscle activity, metabolism, and neuroendocrine regulation. Owing to these multifaceted actions, caffeine may affect perioperative outcomes and complications in both beneficial and adverse ways.This narrative review summarizes current evidence on habitual and perioperative caffeine consumption in the surgical setting, addressing its interactions with anesthetic and analgesic drugs, effects on physiological recovery and wound healing, influence on perioperative risk, and potential impact on surgeons’ alertness and procedural precision.The available studies are limited in number, heterogeneous in design, and frequently inconclusive, which precludes clear clinical recommendations regarding habitual or perioperative caffeine consumption. Further well-designed studies are required to clarify the benefits and risks of caffeine use for both patients and surgical staff and to support the development of evidence-based perioperative guidance.